(untitled) (Research, Society and Development, 2022)
The aim of this study is demonstrate the importance of correct conduct by dentists in the initial care, detection and notification of cases of women victims of domestic violence, as well as the role in the oral rehabilitation. This work was classified as a descriptive literature review and qualitative approach. The review was made using online databases, Pubmed, BBO, ABOL and Scielo. Articles published between 2010 and 2021, in Portuguese and English were revised. After full-text analyses, the review showed that the professionals make inappropriate referrals, referring only to a service/professional (mainly the Women’s Defense Police Station or a psychologist), without following up on the case, which is considered insufficient in cases of violence against women, in addition to going against the principle of integrality. It is concluded that health professionals do not have a satisfactory behavior with patients who are victims of domestic violence, both in case detection and notification, mainly due to lack of preparation, ignorance and distrust of the resolution of cases by the public service, requiring the implementation of debates on the subject in academic and professional environments.